2009
DOI: 10.1007/s00268-009-0293-y
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Outcome of Differentiated Thyroid Carcinoma: Experience in a Developing Country

Abstract: Advance stage at presentation and proportionately high rates of FTC and PDTC contribute to poor outcome of DTC in developing countries. Despite dismal outcome, total thyroidectomy seems to prevent thyroid bed recurrence in surviving patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 48 publications
(73 reference statements)
1
18
0
Order By: Relevance
“…Demographic features of 769 patients with Hashimoto's thyroiditis show a mean age of 41.76 ± 12.49 years, similar to the patients with C-FNAC [45]. In addition, in 302 patients with differentiated thyroid carcinoma (62% papillary thyroid carcinoma), Bhargav et al [46] found that the mean age of the patients was 42 ± 14 years. Younger age in our patients with C-FNAC compared to patients with A-FNAC, may be in relation to higher prevalence of lymphocytic thyroiditis and papillary carcinoma.…”
Section: Discussionmentioning
confidence: 69%
“…Demographic features of 769 patients with Hashimoto's thyroiditis show a mean age of 41.76 ± 12.49 years, similar to the patients with C-FNAC [45]. In addition, in 302 patients with differentiated thyroid carcinoma (62% papillary thyroid carcinoma), Bhargav et al [46] found that the mean age of the patients was 42 ± 14 years. Younger age in our patients with C-FNAC compared to patients with A-FNAC, may be in relation to higher prevalence of lymphocytic thyroiditis and papillary carcinoma.…”
Section: Discussionmentioning
confidence: 69%
“…It remains unclear whether this procedure confers an advantage on overall patient survival when associated with the risk of postoperative complications, such as hypoparathyroidism and recurrent laryngeal nerve injury [2, 3, 814]. Some authors claim that total thyroidectomy adds an unnecessary risk of complications in patients with MND and that postoperative use of thyroid hormone supplementation can be very effective in preventing the recurrence in most patients subjected to function-preserving thyroidectomies [2, 4].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with papillary thyroid cancer (PTC), follicular thyroid cancer (FTC) is more aggressive and harder to diagnose [4]. Although most FTCs can be cured with surgery, the overall 10-year survival rate of FTC is lower than that of PTC [5]. Therefore, understanding the molecular mechanisms of FTC tumours is important for developing better diagnostic strategies and improving the therapeutic outcome of FTC.…”
Section: Introductionmentioning
confidence: 99%